2005
DOI: 10.1016/j.molcel.2004.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Global Impairment of the Ubiquitin-Proteasome System by Nuclear or Cytoplasmic Protein Aggregates Precedes Inclusion Body Formation

Abstract: The highly conserved ubiquitin-proteasome system (UPS) controls the stability of most nuclear and cytoplasmic proteins and is therefore essential for virtually all aspects of cellular function. We have previously shown that the UPS is impaired in the presence of aggregated proteins that become deposited into cytoplasmic inclusion bodies (IBs). Here, we report that production of protein aggregates specifically targeted to either the nucleus or cytosol leads to global impairment of UPS function in both cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
342
4
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(370 citation statements)
references
References 56 publications
19
342
4
5
Order By: Relevance
“…Indeed, several studies have shown that sequestration of metastable and essential cellular factors such as proteins involved in chromatin remodeling, transcription, translation, nuclear import and cytoskeletal structure by the aggregates is the major cause of observed toxicity in vivo (Bucciantini et al, 2002;Chai et al, 2002;Olzscha et al, 2011;Suhr et al, 2001). Aggregates can also interfere with the cellular defense mechanisms by altering protein folding homeostasis (Gidalevitz et al, 2006;Satyal et al, 2000), by blocking proteasome mediated degradation (Bence et al, 2001;Bennett et al, 2005) or by inhibiting autophagy . Other models suggest that the aggregates can engage in aberrant interaction with cellular membranes leading to the formation of membrane pores (Lashuel et al, 2002) or they can disturb cellular ion homeostasis (Quist et al, 2005), may cause mitochondrial dysfunction and oxidative stress (Muller et al, 2010) (Figure 8).…”
Section: Prion Protein Extracellularmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies have shown that sequestration of metastable and essential cellular factors such as proteins involved in chromatin remodeling, transcription, translation, nuclear import and cytoskeletal structure by the aggregates is the major cause of observed toxicity in vivo (Bucciantini et al, 2002;Chai et al, 2002;Olzscha et al, 2011;Suhr et al, 2001). Aggregates can also interfere with the cellular defense mechanisms by altering protein folding homeostasis (Gidalevitz et al, 2006;Satyal et al, 2000), by blocking proteasome mediated degradation (Bence et al, 2001;Bennett et al, 2005) or by inhibiting autophagy . Other models suggest that the aggregates can engage in aberrant interaction with cellular membranes leading to the formation of membrane pores (Lashuel et al, 2002) or they can disturb cellular ion homeostasis (Quist et al, 2005), may cause mitochondrial dysfunction and oxidative stress (Muller et al, 2010) (Figure 8).…”
Section: Prion Protein Extracellularmentioning
confidence: 99%
“…Several studies have documented a role of Htt in causing UPS impairment (Bence et al, 2001;Bennett et al, 2005;Venkatraman et al, 2004). More recently, it was shown that mutant Htt, whether aggregated or not, does not impair the 26S proteasome directly but it leads to the accumulation of ubiquitinated substrates which disrupts cellular proteostasis (Hipp et al, 2012).…”
Section: Vi5 Fluc-based Sensors Report On Proteostasis Collapse By mentioning
confidence: 99%
“…Irreversibly misfolded proteins are toxic to the cell because they trap normal proteins in aggregates and they inhibit the proteasome-dependent protein degradation pathway (Holmberg et al, 2004;Schaffar et al, 2004;Bennett et al, 2005). Mutations that alter amino acid residues often cause protein misfolding, which leads to various diseases, including neurodegenerative disease (Barral et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CCT was shown to inhibit protein aggregation and counteract the cytotoxicity of misfolded proteins (Behrends et al, 2006;Kitamura et al, 2006;Kubota et al, 2006;Tam et al, 2006). These observations indicate that molecular chaperones are indispensable for protecting cells against the pernicious effects of misfolded proteins.Irreversibly misfolded proteins are toxic to the cell because they trap normal proteins in aggregates and they inhibit the proteasome-dependent protein degradation pathway (Holmberg et al, 2004;Schaffar et al, 2004;Bennett et al, 2005). Mutations that alter amino acid residues often cause protein misfolding, which leads to various diseases, including neurodegenerative disease (Barral et al, 2004).…”
mentioning
confidence: 99%
“…Interferon pathways could also be affected by expression of genes related to proteasome, immunoproteasome, and ubiquitin-mediated proteolysis in the 5-9 age group (Supplemental Table S3). These pathways are also involved in neurodegenerative movement disorders including Huntington's Disease (Bennett et al, 2005). B cell and antibody function may also be affected since there is down-regulation of precursor B cell immunoglobulin regions necessary for competent B cell receptor (antibody) rearrangement (e.g.…”
Section: Hypothesis Generation For Further Studymentioning
confidence: 99%